POTENSI PASAR TRADISIONAL DALAM PENINGKATAN EKONOMI MASYARAKAT MENURUTPERSPEKTIF EKONOMI ISLAM (Studi Kasus Pasar Cekkeng di Kab. Bulukumba) - Wahdania, Hera; HR, Agus Salim (Jurnal Ar-Ribh, 2020)
This type of research is classified as qualitative with the research approach used is: a sociological approach because researchers conduct environmental interactions in accordance with social units, Individuals, Groups, Institutions or Society. Furthermore, the data collection methods used are literature survey, observation and interview. Then, data management and analysis techniques are carried out through three stages, namely: Data Collection, Data Reduction, Data Presentation, and the final stage is drawing conclusions. The results of this study indicate that the Cekkeng traditional market has the potential to improve the economy of traders. The Cekkeng market potential is first, the price is cheaper than other traditional markets. Second, the variety of products, time and strategic location. In addition, the supporting factor is the attention of the local government, namely, first, the existence of price controls. Second, preventing fraud in the market such as preventing fraud in scales and size. Third, preventing the sale of damaged goods, and acts that damage morale.